The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1074/jbc.m114.612291
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Atypical Killer Cell Immunoglobulin-like Receptor, KIR2DL4

Abstract: Background: KIR2DL4 is an important natural killer cell receptor with properties distinct from other KIRs. Results: The D0 domain of KIR2DL4 drove self-association of the receptor. Conclusion: Among KIRs, the self-association of KIR2DL4 is unique and a result of discrete differences in its D0 domain. Significance: The self-association of KIR2DL4 has implications for its unique signaling and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…The sixth gene, KIR2DL4 , is expressed on mRNA level in every NK cell but is weakly expressed, if at all, on the cell surface of CD56 dim NK cells . Although originally described as HLA‐G‐specific receptor, recent evidence argues against direct interaction of HLA‐G with KIR2DL4 . Due to the fact that KIR expression in A/A haplotype donors can be fully discriminated by flow cytometry ( Table ), most of the information we presently have about the phenotype and the factors that shape human NK cell repertoires is based on the analysis of donors that are homozygous for group A haplotypes .…”
Section: Composition Of Human Nk Cell Repertoiresmentioning
confidence: 99%
“…The sixth gene, KIR2DL4 , is expressed on mRNA level in every NK cell but is weakly expressed, if at all, on the cell surface of CD56 dim NK cells . Although originally described as HLA‐G‐specific receptor, recent evidence argues against direct interaction of HLA‐G with KIR2DL4 . Due to the fact that KIR expression in A/A haplotype donors can be fully discriminated by flow cytometry ( Table ), most of the information we presently have about the phenotype and the factors that shape human NK cell repertoires is based on the analysis of donors that are homozygous for group A haplotypes .…”
Section: Composition Of Human Nk Cell Repertoiresmentioning
confidence: 99%
“…The structures of seven KIRs (2DL1, 2DL2, 2DS2, 2DL3, 2DL4, 2DS4, and 3DL1) have been determined either in isolation or in complex with a HLA class I protein ( Fig. A–F ).…”
Section: Common Features Of Kir‐hla Interactionsmentioning
confidence: 99%
“…Understanding ligand recognition and signal transduction by KIR2DL4 is further complicated by its largely endosomal localization, a property dependent on its ectodomains . The resolution of the structure of KIR2DL4 showed that like other KIR2D receptors, the D0‐D2 domains of KIR2DL4 adopted a ‘V’ architecture, yet with a less acute hinge angle of approximately 85° relative to that between the D1 and D2 domains in other KIR . Most notably however, unlike other KIR receptors, which exist as monomers in solution, KIR2DL4 was observed as a tetramer ( Fig.…”
Section: D0‐d2 Kir: More Questions Than Answersmentioning
confidence: 99%
“…Such isoforms may act instead of KIR2DL4, which emerged in this study not associated with susceptibility to miscarriage or protection against disease in female patients. Moreover, the studies on the crystal structure of KIR2DL4 showed that this receptor oligomerizes to tetramers possibly because of the absence of D0 domain glycosylation (Moradi et al 2015). This was supposed to preclude an interaction of receptor with HLA.…”
Section: Discussionmentioning
confidence: 99%
“…This was supposed to preclude an interaction of receptor with HLA. Indeed, Moradi et al (2015) were unable to detect an interaction between KIR2DL4 and a panel of 100 pHLA-Ia or HLA-G by single HLA-antigen bead assay and by surface plasmon resonance. Therefore, a self-association of KIR2DL4 could regulate ligand binding and subsequent signal transduction.…”
Section: Discussionmentioning
confidence: 99%